0465 Exploring Differences in Self-Report Sleep Measures in Adults with Insomnia who Use or Do Not Use Sleep Medication. (25th May 2022) - Tutek, Joshua; Tully, Isabelle; Simpson, Norah; Manber, Rachel
Abstract: Introduction: Adults seeking non-pharmacological treatment for insomnia often present for care already taking prescription medication for sleep. Understanding how such patients differ from those who do not use medication could be useful for guiding treatment. This study examined associations between sleep medication use and measures of self-report sleep characteristics at baseline in an RCT of cognitive behavioral therapy for insomnia (CBTI). Methods: We examined baseline data from 237 middle-to-older-aged adults with insomnia disorder (175 women, M age = 63.17) enrolled in the ongoing RCT on Effectiveness of Stepped-Care Sleep Therapy (RESTING). Participants were dichotomized by whether they reported taking at least one prescription medication for sleep. Sleep measures included the Insomnia Severity Index (ISI), PROMIS Sleep-Related Impairment short form, Epworth Sleepiness Scale (ESS), Cognitive Presleep Arousal Scale, Dysfunctional Attitudes and Beliefs About Sleep Scale, and two weeks of sleep diaries yielding average nightly sleep onset latency, wake time after sleep onset, total sleep time, and sleep quality ratings. MANOVA compared medication users and non-users across sleep measures. Results: Seventy-seven (32.5%) participants reported taking at least one prescription medication for sleep at baseline. MANOVA results indicated that sleep measures collectively differed by medication use, F(9, 226) = 3.74, p < .001; Wilk's Λ = .87, partial η-sqd = .13. Bonferroni-adjusted follow-up comparisons (p < .005) found that only ESS significantly differed between medication users and non-users, F(1, 234) = 15.17, p < .001; partial η-sqd = .06. Medication users had lower sleepiness scores (M = 5.86, SD = 4.68) than non-users (M = 8.46, SD = 4.84). The association between medication use and less daytime sleepiness was maintained after adjusting for ISI. Conclusion: Sleep medication use displayed little association with sleep measures in adults about to undergo CBTI, excepting endorsement of less daytime sleepiness by medication users. While more research is needed to understand the implications of sleep medication use for adults engaging in CBTI, these initial findings suggest that CBTI therapists should be thoughtful about sleepiness in non-medication users, and the potential emergence of sleepiness among patients who engage in sleep medication taper while in treatment. Support (If Any): 1R01AG057500